An analysis of a structured benchmarking project: The case of Dubai Electricity and Water Authority's benchmarking project. Issue 5 (1st July 2019) - Al Nuseirat, Ahmad Abdullah; El Kahlout, Zeyad Mohammad; Abbas, Ahmed; Adebanjo, Dotun; Punnakitikashem, Prattana; Mann, Robin
Abstract : Purpose: The purpose of this paper is to investigate a benchmarking project carried out by the Dubai Electricity and Water Authority (DEWA) as part of a structured benchmarking initiative. The project was based on the TRADE benchmarking methodology and this paper examines the tools, activities and outcomes that relate to each stage of the adopted methodology. Design/methodology/approach: This study is based on case study methodology. Data were collected from various sources including analysis of project reports written by DEWA's benchmarking team reporting on their activities during the project. Data were also collected from four project presentations given at different stages of the project. In addition, the research team held three meetings with the DEWA benchmarking team at different stages of the benchmarking project. Findings: The results show the key challenges and successes faced during each stage of the benchmarking project. It indicates the actions taken to overcome the challenges and the role played by internal and external stakeholders in facilitating the success of the benchmarking project. Practical implications: The study presents information that would guide organisations that wish to carry out a benchmarking project – and particularly those implementing benchmarking for the first time. The study provides a summary of the key lessons learnt by DEWA's benchmarking team as a guide for other organisations. Originality/value: Academic research has not adequately examined and analysed the stage-by-stage elements of a benchmarking project from the perspective of the implementing organisation. This study addresses this gap by detailing and analysing the experiences of a benchmarking project by tracking the stage-by-stage activities of the benchmarking team.